Blighted Spaces and the Politics of Everyday Life - Robert Fairbanks (Social Work & Society, 2003)
While a great deal is known about the demographic and historical trends that shape the built environment of American cities, much less is known about the politics of everyday life among residents who continue to live in postindustrial neighborhoods. This study seeks to compensate for the current gaps in academic research by conducting spatially informed ethnography in a North Philadelphia community. Specifically, the study will explore the issue of urban "blight" from a cultural geography perspective, primarily by looking at the ways in which "blighted" spaces shape everyday life, and everyday life in turn shapes and produces the spatial environment. In response to these concerns, my study poses the questions: What would it mean to focus on the ways in which human agency, imagination, and subjectivity are shaped by "blighted" geographical locations? What would it mean to pay ethnographic attention to how subjects in given historical conditions are shaped by "blighted" spaces, as well as how they respond to these spaces in culturally specific ways? By incorporating critical interdisciplinary approaches, this study offers a new way of looking at the various practices of daily life - including flexible, informal economic activities and post-welfare related "lifestyles" of resistance. Through the lens of spatial ethnography, the study seeks to elucidate the ways in which postindustrial space interacts with culture, poverty and addiction; as well as the ways in which users continue to appropriate postindustrial spaces in culturally meaningful ways under the aegis of the semi-welfare state.